Bending and Deformation of Sandwich Panels Due to Localized Pressure - Bambang K. Hadi; A. Fajar (Journal of Engineering and Technological Sciences, 2005)
Bending and deformation of sandwich panels due to localized pressure were analyzed using both Rayleigh-Ritz and finite element methods. The faces were made of laminated composite plates, while the core was a honeycomb material. Carbon fiber and glass fiber reinforced plastics were used for composite plate faces. In the case of Rayleigh-Ritz method, first the total energy of the system was calculated and then taking the variations of the total energy, the sandwich panel deflections could be computed. The deflections were assumed by means of Fourier series. A finite element code NASTRAN was exploited extensively in the finite element method. 3-dimensional 8-node brick elements were used to model sandwich panels, for both the faces sheets and the core. The results were then compared to each other and in general they are in good agreements. Dimple phenomena were found in these cases. It shows that localized pressure on sandwich structures will produce dimple on the pressurize region with little effects on the rest of the structures.